Information and Communication Technologies in Primary Education: Teachers’ Perceptions in Greece - Marina Aivazidi; Christos Michalakelis (Informatics, 2023)
Innovative learning methods including the increasing use of Information and Communication Technologies (ICT) applications are transforming the contemporary educational process. Teachers’ perceptions of ICT, self-efficacy on computers and demographics are some of the factors that have been found to impact the use of ICT in the educational process. The aim of the present research is to analyze the perceptions of primary school teachers about ICT and how they affect their use in the educational process, through the case of Greece. To do so, primary research was carried out. Data from 285 valid questionnaires were statistically analyzed using descriptive statistics, principal components analysis, correlation and regression analysis. The main results were in accordance with the relevant literature, indicating the impact of teachers’ self-efficacy, perceptions and demographics on ICT use in the educational process. These results provide useful insights for the achievement of a successful implementation of ICT in education.